PENGARUH TAYANGAN PROGRAM 86 DI NET TV TERHADAP CITRA KEPOLISIAN REPUBLIK INDONESIA PADA SISWA SEKOLAH MENENGAH KEJURUAN TARUNA SATRIA PEKANBARU - Ade Fadhli; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The 86 program on NET TV shows the duties of police officers and their daily activities in carrying out their duties such as curbing traffic violators, fostering people who have violated the rules of order, and disclosing drug syndicates in various regions. The purpose of this study was to determine the effect of program 86 on NET TV on the image of the Republic of Indonesia Police in Pekanbaru Satuna Vocational School students as well as how much influence the 86 TV program on the image of the Republic of Indonesia Police on SMK Satuna Pekanbaru students.The method used in this research was quantitative explanatory. Questionnaires was used for collecting the data of the research.  The study was conducted at SMK Taruna Satria Pekanbaru. There were 166 respondents as the sample of this research. The sampling technique used accidental sampling. The theory used in this study was the Stimulus Response theory. The analysis test used in this study was simple linear regression analysis and to processed the questionnaire data, carried out by using SPSS for Windows version 19. The results obtained from the simple linear regression analysis in this study are that there is a significant effect between Program 86 Impressions on Net TV Against Republic of Indonesia Police Images to Students of SMK Taruna Satria Pekanbaru and the magnitude of the influence between 86 Program Impressions on Net TV Against the Indonesian Police at the Students of SMK Taruna Satria Pekanbaru amounting to 60.7% which is categorized as a strong influence, while the remaining 39.3% is influenced by other factors not used in this study. Keywords: Impressions, , 86, The Image Of Police, SMK Taruna Satria Pekanbaru